Integrating Human and Wildlife Dynamics in Co‐Occurrence Modelling - F. Rolle; M. V. Boiani; L. Fardone; F. Gaydou; M. Macario; F. Parentela; V. Ruco; D. Sigaudo; F. Marucco (Ecology and Evolution, 2025)
ABSTRACT In shared environments, where different species interact depending on overlapping resources, complex interspecific interactions emerge, with human activities impacting these dynamics and influencing wildlife abundance and distribution. In the Alps, the presence of multiple species of ungulates, such as roe deer and red deer, and a predator, the wolf, creates a web of spatial and behavioral interactions in an area where farming, hunting and tourism have persisted over time, with tourism recently experiencing a substantial growth. Accounting for these multiple interactions, we modelled the co‐occurrence probabilities of roe deer, red deer and wolves in an area of the Maritime Alps using data derived from 60 camera traps. We applied multi‐species occupancy models to investigate (i) the role of species co‐occurrences in explaining the occupancy of model species across the landscape, (ii) the role of human presence and activities on species occupancy and (iii) the potential effect of the hunting season on the species detection probabilities. Among the identified species, roe deer reported the highest frequency of recorded events and were the most widespread species. We provided important evidence of interspecific dependence, revealing that pairwise interactions among species had a greater impact than only considering individual environmental effects. We documented that the setting of cameras on trails increased the likelihood of detecting wolves but decreased the likelihood of detecting ungulates. Most importantly, the hunting season significantly reduced the likelihood of capturing roe deer, while having no effect on either red deer or wolves. Our results confirmed the relevance of including prey, predators, and human dynamics as a whole. Since the sharing of habitat makes human activities significantly important in defining predator–prey mechanisms, our insights are particularly relevant for defining solutions to optimize human‐wildlife coexistence, especially in a highly anthropogenic system such as Europe.